Teachers’ Attitude towards Virtual Teaching and Learning Process during the Covid-19 Pandemic in Pakistan: A Questionnaire-Assisted Discourse Study - Saqlain Hassan,; Jamshaid Anjum,; Hira Bari,; Mahnoor Asim,; Ayesha Sattar,; Sidra Kousar, (Al-Qanṭara, 2024)
The COVID-19 pandemic's impact was felt worldwide, and its effects are expected to last for decades. One of the main concerns during the pandemic was ensuring continued education for students and teachers despite the lockdowns in affected countries. Consequently, educational institutions were forced to close off and on, and teaching and learning had to be rescued by digital media such as Zoom, Skype, and Team. However, in Pakistan, most places do not have internet access, and teachers are not accustomed to virtual teaching. As the restrictions and lockdowns persisted, distance education became necessary, and teachers adopted it as a common routine. This study aims to observe teachers' attitudes towards virtual teaching, their experiences during the pandemic, how they overcame technology-related issues, and how they envision the future of virtual teaching or blended-learning techniques in their on-campus teaching activities after the pandemic.